Modelling of Blood Lactate Time-Courses During Exercise and/or the Subsequent Recovery: Limitations and Few Perspectives - Durand, Rémi; Galli, Mayeul; Chenavard, Marie; Bandiera, David; Freund, Hubert; Messonnier, Laurent A. (Frontiers in Physiology, 2021)
Because lactate is an important metabolic intermediate as well as a signaling molecule between/within cells/organs, it appears essential to be able to describe the kinetics of this central molecule, during and/or after physical exercise. The aim of the present study was to confront three models and their approaches [Freund and co-workers (F&co), Beneke and co-workers (B&co) and Quittmann and co-workers (Q&co)] to investigate the lactate exchange (γ1) and removal (γ2) abilities (min-1) during and/or after exercise. Nine healthy male subjects performed 3- and 6-min easy, moderate and heavy exercise. Blood lactate concentration was measured every 5 s over the entire period of exercise and recovery. Approaches differ depending on the domain in which the model is applied: considering exercise and part of the recovery (B&co and Q&co) or the entire period of recovery (F&co). The different approaches result in differing γ1 and γ2 values. Model fitting is closer to the experimental values following the method (model and approach) of F&co. Complementary analyses show that consideration of i) exercise drastically impairs the quality of model fitting and therefore the γ1 and γ2 values and ii) the entire period of recovery considerably improves the quality of fits and therefore of the γ1 and γ2 values. We conclude that i) it is neither realistic nor reliable to take into account exercise and recovery in the same model and ii) the longer the period of recovery studied, the better the quality of the γ1 and γ2 values.